Plasma procalcitonin concentration in healthy calves and those with septic systemic inflammatory response syndrome. (April 2018) - Bonelli, F.; Meucci, V.; Divers, T.J.; Boccardo, A.; Pravettoni, D.; Meylan, M.; Belloli, A.G.; Sgorbini, M.
Highlights: Procalcitonin (PCT) has been investigated as biomarker of sepsis in humans and different animal species. Procalcitonin was evaluated in healthy calves and those with septic systemic inflammatory response syndrome (SIRS). Plasma PCT concentration was higher in the septic SIRS group than in the healthy group. Plasma PCT levels were increased in septic SIRS calves, as reported in humans and other species. PCT could be used as marker for septic SIRS in calves. Abstract: The diagnosis of sepsis in calves is challenging. Blood culture and clinical signs combined with a complete blood count have been used for the diagnosis of sepsis. Recent literature in humans and animal species has been focused on sepsis-specific biomarkers, such as procalcitonin (PCT), that may more accurately and efficiently diagnose sepsis. The aim of this study was to evaluate plasma PCT concentrations in healthy and septic calves. Twenty healthy control calves and 58 sick calves with septic systemic inflammatory response syndrome (SIRS) based on SIRS score and clinical findings were included. Calves with septic SIRS were further divided in septic SIRS survivors (SSS) and non-survivors (SSNS). Plasma PCT concentrations were measured with a commercial ELISA assay for cattle. A receiver operating characteristic curve was used to determine cut-off values and corresponding sensitivity and specificity for the diagnosis of sepsis. Differences in plasma PCT concentration between groups (control vs. SSS vs. SSNS) were evaluated. Plasma PCT concentrations in healthy calves and those with septic SIRS were 33.3 pg/mL (0–44.3 pg/mL) and 166.5 pg/mL (85.9–233.0 pg/mL), respectively ( P < 0.001). The optimal cut-off value to predict septic SIRS was 67.39 pg/mL (81.0% sensitivity, 95.0% specificity). Plasma PCT concentrations were 127.4 pg/mL (72.2–216.0 pg/mL) and 234.3 pg/mL (204.5–309.4 pg/mL) in the SSS and SSNS subgroups, respectively. Statistically significant differences were found among groups (control vs. SSS and SSNS, P < 0.0001; SSS vs. SSNS, P > 0.05). These results confirmed an increase in plasma PCT concentrations in calves with septic SIRS, as previously reported in humans and other species.